Correlation between occlusal vertical dimension and finger length in an adult Tumbesian population - González-Orellana, Diana Katherin; Rendón-Alvarado, Alfredo Carlos Manuel (Revista Facultad de Odontología Universidad de Antioquia, 2025)
Introduction: In oral rehabilitation, multiple methods have been described to obtain the Vertical Occlusal Dimension (VOD), some based on aesthetics, others using functional, cephalometric, anthropometric, and facial craniometric approaches; but despite this multiplicity of methods, none seems more accurate or more reliable than another. The objective of the study was to determine if there is a correlation between the occlusal vertical dimension and the length of the fingers of the hand in an adult population of Tumbes in 2023. Methods: The design was cross-sectional correlational; 198 subjects participated, between 18 and 30 years of age. The VOD and the length of the fingers were measured using a digital vernier, and then the measurements were correlated with the statistical test of Pearson’s R. Results: It was found that there is a correlation between the DVO and the length of the fingers, with the highest correlation being found with the second finger of the right hand (index) r = 0.652. The mean of the VOD was 71.85 mm, and the phalanx closest to the VOD was that of the left ring finger with 71.27 mm; in addition, there are significant differences in the VOD according to sex; the estimated regression formulas for males were VOD = 43.633 + 0.419 * LongD2D (right index), also VOD = 47.605 + 0.327 * LongD1D (right thumb); and in women, VOD = 34.404 + 0.545 * LongD2D (right index), also VOD = 37.296 + 0.584 * LongD5D (right pinky). Conclusion: There is a high positive correlation between VOD and the length of the fingers, with the right index finger and thumb having the highest correlation in men and the index and little fingers in women.